Approaching sites of action of temozolomide for pharmacological and clinical studies in glioblastoma - Fresnais, Margaux; Turcan, S̨evin; Theile, Dirk; Ungermann, Johannes; Abou Zeed, Yasmin; Lindner, Joshua Raoul; Breitkopf, Marius; Burhenne, Jürgen; Haefeli, Walter E.; Longuespée, Rémi (Biomedicines, 2022)
Temozolomide (TMZ), together with bulk resection and focal radiotherapy, is currently a standard of care for glioblastoma. Absorption, distribution, metabolism, and excretion (ADME) parameters, together with the mode of action of TMZ, make its biochemical and biological action difficult to understand. Accurate understanding of the mode of action of TMZ and the monitoring of TMZ at its anatomical, cellular, and molecular sites of action (SOAs) would greatly benefit precision medicine and the development of novel therapeutic approaches in combination with TMZ. In the present perspective article, we summarize the known ADME parameters and modes of action of TMZ, and we review the possible methodological options to monitor TMZ at its SOAs. We focus our descriptions of methodologies on mass spectrometry-based approaches, and all related considerations are taken into account regarding the avoidance of artifacts in mass spectrometric analysis during sampling, sample preparation, and the evaluation of results. Finally, we provide an overview of potential applications for precision medicine and drug development.